P and Ca requirements for Japanese quail. Issue 2 (17th March 2016) - Mariz, C. B. L.; Silva, J. H. V.; Filho, J. J.; Lima, M. R.; Costa, F. G. P.
Summary: Four experiments were conducted to estimate the phosphorus and calcium requirements for weight maintenance and weight gain in Japanese quails during their growth phase from 16 to 36 days. Japanese quails aged 16 days were used for estimating the phosphorous and calcium requirements for weight maintenance or weight gain, with these quails composing each reference slaughter group and the others distributed in a completely randomized design, housed in cages of galvanized wire (33 × 33 × 16 cm) that were stored in acclimatized chambers with specific environmental temperatures. The light programme used during the 20‐day experimental period was 24 h of artificial light. Analysis of the data showed that the prediction equations for estimating the phosphorus and calcium requirements for weight maintenance and weight gain of Japanese quails between 16 and 36 days of age were P (g/quail/day) = P 0.75 *(9.3695 + 7.7397*T) + 9.70*WG, in which P is the phosphorus requirement, and Ca (g/quail/day) = P 0.75 *(363.99 – 8.0262*T) + 28.15*WG, in which Ca is the calcium requirement, P is BW (kg), T is temperature (°C) and WG (g/quail/day).